The Effect of Auditor's Competence, Professionalism, and Organizational Culture on the Quality of Financial Statements - Ly Lian; R Wedi Rusamawan Kusumah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Human resources have a significant role in the quality of financial reporting. The existence of competent and independent human resources has a wide level of description of the company's financial management. This study purposes to analyze the factors that affect the quality of company financial reporting in some industries in Bandung, by observing at organizational culture and internal audit quality as seen from the auditor professionalism and competence. This research was conducted on 95 employees of the finance department at a private company in Bandung. The data in this research applied primary information in the form of observation and distribution of questionnaires to individuals’ respondents. The findings of this study indicate that the competence and professionalism of the auditor, as well as the organizational culture of the company, will determine the quality of the company's financial reporting. The better the competence and professionalism of the auditor, the higher the quality of the financial reporting. In addition, the existence of a conducive and supportive organizational culture will increase the quality of financial reports.